The Effect of Acupressure Massage At LI 4 Point on Menstrual Pain Among Female Adolescents in Bogor Regency - Yenny Aulya; Suprihatin; Arini Gardinia Latifah; Bunga Tiara Carolin (Rajaki of Tulip Medika Publisher, 2025)
Primary menstrual pain accounts for a prevalence of 89.5% of all menstrual disorders. In Indonesia, 54.89% of women suffer from primary menstrual pain. Untreated pain can cause worsening conditions such as headache, vomiting, fatigue, and diarrhea. One of the non-pharmacological methods to reduce pain is acupressure massage. Objective: This study intends to determine the effect of acupressure massage at point LI (Large Intestine) 4 on menstrual pain in adolescent girls in Bogor Regency. Methodology: The design of this study is quasi-experimental with a two-group pretest-posttest control group design. A sample of 30 respondents aged 14-22 years who experienced primary menstrual pain on the first and second days of menstruation, was selected by purposive sampling technique. The instrument used is the Numeric Rating Scale (NRS). The data was analyzed using the Paired Sample T-Test and Independent T-Test. . The average level of menstrual pain in adolescent girls in the intervention group was obtained with a pretest score of 5.80 and a posttest score of 3.53. The average level of menstrual pain in adolescent girls in the control group had a pretest score of 6.33 and a posttest score of 6.20. In both the Paired Sample T-Test and the Independent T-Test, the p-value of the intervention group was obtained of 0.000 < 0.05 so that it can be said that there is an effect of the application of acupressure massage at point LI 4 on the menstrual pain of adolescent girls. Conclusion: There is an effect of the application of acupressure massage at point LI 4 on the reduction of menstrual pain in adolescent girls in the Bogor Regency area Suggestion: Hopefully in the future there will be counseling or seminars for adolescent girls so that they can apply acupressure massage at point LI 4 at home as an alternative to complementary therapy.